Experiences of living with varicose veins: A systematic review of qualitative research. Issue 7 (14th December 2018) - Lumley, Elizabeth; Phillips, Patrick; Aber, Ahmed; Buckley‐Woods, Helen; Jones, Georgina L.; Michaels, Jonathan A.
Abstract: Aim: To identify the symptoms and quality of life impacts that are important from the perspective of patients with varicose veins and to compare identified themes to items in varicose vein patient‐reported outcome measures (PROMs). Background: Varicose veins are common worldwide and are considered a chronic condition with implications for quality of life. Treatment is predominantly conservative; therefore, understanding patients' experiences of living with varicose veins is important to inform the provision of clinical care. PROMs are often used to collect data about patients' quality of life. Design: Thematic synthesis of qualitative research reported according to ENTREQ guidelines. Methods: Multiple electronic databases, including MEDLINE and CINAHL, were systematically searched to identify qualitative research examining experiences of adults with varicose veins. Thematic synthesis was then conducted on the included studies. Results: Three studies met the inclusion criteria; the quality of the studies was high. The range and intensity of reported symptoms and participant's experiences of living with varicose veins were varied. Five overarching themes were identified: physical, psychological and social impact of varicose veins, adapting to varicose veins and reasons for seeking treatment. The overall key theme to emerge was adaptation, with patients demonstrating how they adapted to the various impacts. Conclusion: This review demonstrates that varicose veins have a wide range of symptoms and may have a significant impact on quality of life; people made significant adaptations to enable them to live their lives as fully as possible. Relevance to Clinical Practice: Healthcare professionals need to be aware of the range of symptoms and their impact on quality of life. The use of PROMs to gather information about quality of life and symptoms is well established globally; however, PROMs currently used may not capture the full extent of the impact on patient's quality of life.